2000
DOI: 10.1177/0887302x0001800104
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Students' Integration of Textiles and Clothing Subject Matter Part One: Dimensions of a Model and a Taxonomy

Abstract: Scholars have written literature elucidating the integration of textiles and clothing subject matter. However, this literature does not clearly explicate how students can integrate subject matter or how integration can serve professional development of students. The purpose of part one of a two part paper is to describe elements of two learning aids, a model and a taxonomy, that may be used to help students conceptually integrate textiles and clothing subject matter and assist their professional development. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Other studies also examined recreational attributes, such as atmosphere (Donovan and Rossiter, 1982), the importance of pleasure in a shopping experience (Dawson et al, 1990) and the social aspects of mall shopping (Jarboe and McDaniel, 1987). One study found that satisfaction with store environment, a key indicator of future patronage, was a direct result of behavior and mood (Babin and Darden, 1995;Fiore and Ogle, 2000). Fiore and Ogle (2000) argue that formal, expressive and symbolic qualities of store environments communicate various messages to consumers about both aesthetics and instrumental value.…”
Section: Attitude Toward Mall Attributesmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies also examined recreational attributes, such as atmosphere (Donovan and Rossiter, 1982), the importance of pleasure in a shopping experience (Dawson et al, 1990) and the social aspects of mall shopping (Jarboe and McDaniel, 1987). One study found that satisfaction with store environment, a key indicator of future patronage, was a direct result of behavior and mood (Babin and Darden, 1995;Fiore and Ogle, 2000). Fiore and Ogle (2000) argue that formal, expressive and symbolic qualities of store environments communicate various messages to consumers about both aesthetics and instrumental value.…”
Section: Attitude Toward Mall Attributesmentioning
confidence: 95%
“…One study found that satisfaction with store environment, a key indicator of future patronage, was a direct result of behavior and mood (Babin and Darden, 1995;Fiore and Ogle, 2000). Fiore and Ogle (2000) argue that formal, expressive and symbolic qualities of store environments communicate various messages to consumers about both aesthetics and instrumental value. Baker et al (1994) report that environment may influence consumer inferences about merchandise, service quality and store image.…”
Section: Attitude Toward Mall Attributesmentioning
confidence: 97%
“…In addition, consumers consider the interplay o f apparel products and the body when shopping on apparel websites (Levaux, 2001). Products featured on a body form, showing how they fit on an actual body, lets shoppers virtually "try on" clothing and helps shoppers fantasize about wearing the clothing ("Anthropologic," 2005;Fiore & Ogle, 2000;Levaux, 2001). Also, images o f apparel products on a model's body in an imagery-rich setting (i.e., a country or city scene) offer the consumer a lifestyle-oriented experience, more than images of goods alone, by letting the consumer imagine where the apparel products may be worn ("Anthropologie," 2005).…”
Section: Experiential Marketing and Product Presentationmentioning
confidence: 99%
“…These consumer perceptions, in turn, influence their behavioral responses. For customers to be satisfied, they must perceive that the product and/or environment meet or surpass their desired value (Fiore & Ogle, 2000). However, consumers respond to store environments differently because of their own experience and goals.…”
Section: Organism: Older Consumers' Internal Evaluationsmentioning
confidence: 99%